1991
DOI: 10.1038/ki.1991.255
|View full text |Cite
|
Sign up to set email alerts
|

Early renal medullary hypoxic injury from radiocontrast and indomethacin

Abstract: We evaluated the acute changes in cortical and outer medullary oxygen tension and the alterations in renal function and morphology within the first 90 minutes after the administration of indomethacin and iothalamate to anesthetized Sprague-Dawley rats. Both agents were found to produce marked and protracted outer medullary hypoxia averaging 12 +/- 4 and 9 +/- 2 mm Hg, respectively (mean +/- SE). Given together to salt depleted uninephrectomized rats they produced an early hypoxic injury localized selectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 279 publications
(206 citation statements)
references
References 27 publications
6
192
1
2
Order By: Relevance
“…Injection of contrast medium promotes secretion of endothelin, a vasoconstrictor peptide produce by endothelial cells, by the renal parenchyma and the resulting vasoconstriction reduces renal tissue blood flow and oxygen supply 9. Also, the osmotic pressure is elevated by infusion of contrast medium, which increases the amount of NaCl reaching the ascending limb of the loop of Henle, and increased sodium reabsorption accelerates renal oxygen consumption.…”
Section: Areas Where Clinical Application Of Hydrogen Gas Is Expectedmentioning
confidence: 99%
“…Injection of contrast medium promotes secretion of endothelin, a vasoconstrictor peptide produce by endothelial cells, by the renal parenchyma and the resulting vasoconstriction reduces renal tissue blood flow and oxygen supply 9. Also, the osmotic pressure is elevated by infusion of contrast medium, which increases the amount of NaCl reaching the ascending limb of the loop of Henle, and increased sodium reabsorption accelerates renal oxygen consumption.…”
Section: Areas Where Clinical Application Of Hydrogen Gas Is Expectedmentioning
confidence: 99%
“…The decline in outer medullary Po 2 , despite enhanced regional blood flow (outlined next), only emphasizes the important role for increased reabsorptive activity in the consequent regional hypoxia. Indeed, as shown in Figure 1, the inhibition of transport activity with the loop diuretic furosemide abruptly reverses radiocontrast-induced medullary hypoxemia (7,18). Furosemide-related attenuation of medullary hypoxemia takes place despite the profound regional vasoconstriction induced by this agent (19), again emphasizing the crucial role of regulated tubular transport activity in the determination of medullary oxygenation.…”
Section: Radiocontrast Agents Increase Renal Oxygen Demandmentioning
confidence: 99%
“…Using oxygen microelectrodes, Brezis and colleagues (7) found that after the injection of the high-osmolar ionic agent sodium iothalamate, cortical Po 2 declined from 40 to 25 mmHg. In the already hypoxic outer medulla, Po 2 fell from 26 mmHg at baseline to mean levels as low as 9 mmHg.…”
Section: Physiologic Medullary Hypoxia Aggravated By Radiocontrast Amentioning
confidence: 99%
See 1 more Smart Citation
“…These include sepsis that induces renal vasoconstriction through the release of endothelin and the use of radiocontrast imaging dyes that increase oxygen consumption for solute reabsorption and reduce regional inner medullary blood flow. [54][55][56][57][58][59][60][61] More generalized reductions in blood flow represent another major cause of AKI. These can result from hemorrhage, decompensated liver cirrhosis, treatment with non-steroidal anti-inflammatory drugs, congestive heart failure, and renal artery occlusion or stenosis.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%